MODEL TOLERANSI PROPHETIK DI MADINAH PASCA HIJRAH DAN RELEVANSINYA TERHADAP PLURALITAS SOSIAL BUDAYA INDONESIA - Muhamad Lutfi; Norfaridatunnisa; Baihaki; Mahrus Alwi Hasan Siregar (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2021)
Tolerance between religious communities is an important issue to be discussed. This is because in recent years various acts of radicalism and tolerance in the name of religion have increasingly occurred in various parts of the world. This study aims to analyze the inter-religious tolerance model practiced by the Prophet Muhammad in Medina. Using a qualitative method with a literature review approach, this research found that the tolerance built by the Prophet in Medina was dominant with the positive-active tolerance model. This study also found that the reality of tolerance in Medina is basically relevant to the plurality of religions in Indonesia. Therefore, the tolerance model developed by the Prophet in Medina is relevant to be implemented in Indonesia. Of course, the implementation of the tolerance model is by adjusting the sociocultural construction of today's society.